Multimedia Tafsir: Exploring the Meaning of the Quran in the Digital Era - Andri Nirwana (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2024)
Embedded within the Quran in the digital era. With the proliferation of digital platforms, multimedia Tafsir offers a dynamic and immersive means to engage with the sacred text, leveraging a myriad of audio, visual, and interactive elements. Through a comprehensive review of existing literature and analysis of case studies, this study delves into the potential impact, challenges, and opportunities presented by multimedia Tafsir in facilitating a deeper understanding of the Quranic teachings. Furthermore, it examines the ethical considerations surrounding the digital dissemination of religious knowledge and the implications for traditional modes of interpretation. By shedding light on the evolving landscape of Quranic interpretation in the digital age, this research contributes to the ongoing discourse on the intersection of technology, religion, and culture.